The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fpsyt.2018.00099
|View full text |Cite
|
Sign up to set email alerts
|

Increased Insular Cortical Thickness Associated With Symptom Severity in Male Youths With Internet Gaming Disorder: A Surface-Based Morphometric Study

Abstract: With the rising increase in Internet-usage, Internet gaming disorder (IGD) has gained massive attention worldwide. However, detailed cerebral morphological changes remain unclear in youths with IGD. In the current study, our aim was to investigate cortical morphology and further explore the relationship between the cortical morphology and symptom severity in male youths with IGD. Forty-eight male youths with IGD and 32 age- and education-matched normal controls received magnetic resonance imaging scans. We emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In VBM study revealed a greater GM volume in the MTG of subjects with IGD . A recent surface-based morphometric study reported increased cortical thickness in the bilateral insula and right IFG and decreased thickness in the bilateral STG of subjects with IGD (Wang et al 2018). fMRI studies of addiction using executive function tasks reported similar results.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
See 1 more Smart Citation
“…In VBM study revealed a greater GM volume in the MTG of subjects with IGD . A recent surface-based morphometric study reported increased cortical thickness in the bilateral insula and right IFG and decreased thickness in the bilateral STG of subjects with IGD (Wang et al 2018). fMRI studies of addiction using executive function tasks reported similar results.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…The increased functional connection between the left frontoparietal network and anterior insula predicts steeper devaluation of delayed rewards in smokers (Clewett et al 2014). Some IGD studies focused on this area have shown that impaired anterior insular activation is associated with poor risky decision making (Lee et al 2016), and increased insular cortical thickness is associated with symptom severity in IGD (Wang et al 2018). Our findings also provide evidence that the insula contributes to how addicted individuals feel (craving), remember, control, and make decisions about (risk-reward decision) their addictive behaviors (Naqvi and Bechara 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of included studies [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and Table 2 shows gray matter regions displaying significant differences between PUI and control groups for each study. Across the whole identified literature, six studies reported the use of a diagnostic interview to confirm PUI (Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 99%
“… 22 Finally, adolescents with IGD showed decreased cortical thickness in distributed cerebral areas and had a positive correlation between the left insular cortical thickness and symptom severity. 23 …”
Section: Cortical Thicknessmentioning
confidence: 99%